Vitamin D and K2 in Tooth Remineralization: New Perspective on Caries Prevention - Fauziah, Yessy Andriani; Darmadi, Eveline Yulia (Universitas Ibn Khaldun Bogor, 2025)
Dental caries remains a significant global health issue, primarily caused by an imbalance between demineralization and remineralization of tooth structures. While fluoride has been the primary agent in caries prevention, recent studies highlight the importance of nutritional factors, particularly vitamin D and K2, in promoting tooth remineralization. These vitamins are critical in calcium metabolism, extracellular matrix regulation, and enamel and dentin mineralization. However, research on their synergistic effects in caries prevention remains limited. The potential integration of vitamins D and K2 into the framework of preventive dentistry could represent a groundbreaking and innovative strategy aimed at augmenting the remineralization process and subsequently mitigating the overall risk of developing caries among individuals. Vitamin D and K2 are essential for tooth remineralization, but the combined impact of vitamin D and K2 in preventing caries is scarce. Integrating vitamin D and K2 into preventive dentistry may offer a novel strategy for enhancing remineralization and reducing caries risk. Further clinical studies are needed to establish evidence-based recommendations.